A New Framework for Automatic Detection of Patients With Mild Cognitive Impairment Using Resting-State EEG Signals - Siuly, Siuly; Alcin, Omer Faruk; Kabir, Enamul; Sengur, Abdulkadir; Wang, Hua; Zhang, Yanchun; Whittaker, Frank (Ieee-Inst Electrical Electronics Engineers Inc, 2020)
Mild cognitive impairment (MCI) can be an indicator representing the early stage of Alzheimier's disease (AD). AD, which is the most common form of dementia, is a major public health problem worldwide. Efficient detection of MCI is essential to identify the risks of AD and dementia. Currently Electroencephalography (EEG) is the most popular tool to investigate the presenence of MCI biomarkers. This study aims to develop a new framework that can use EEG data to automatically distinguish MCI patients from healthy control subjects. The proposed framework consists of noise removal (baseline drift and power line interference noises), segmentation, data compression, feature extraction, classification, and performance evaluation. This study introduces Piecewise Aggregate Approximation (PAA) for compressing massive volumes of EEG data for reliable analysis. Permutation entropy (PE) and auto-regressive (AR) model features are investigated to explore whether the changes in EEG signals can effectively distinguish MCI from healthy control subjects. Finally, three models are developed based on three modern machine learning techniques: Extreme Learning Machine (ELM); Support Vector Machine (SVM) and K-Nearest Neighbours (KNN) for the obtained feature sets. Our developed models are tested on a publicly available MCI EEG database and the robustness of our models is evaluated by using a 10-fold cross validation method. The results show that the proposed ELM based method achieves the highest classification accuracy (98.78%) with lower execution time (0.281 seconds) and also outperforms the existing methods. The experimental results suggest that our proposed framework could provide a robust biomarker for efficient detection of MCI patients.
Keywords: Electroencephalography; Brain modeling; Dementia; Feature extraction; Aggregates; Biological system modeling; Mild cognitive impairment (MCI); Alzheimer's disease (AD); electroencephalogram (EEG); piecewise aggregate approximation (PAA); auto-regressive (AR) model; permutation entropy (PE); extreme learning machine (ELM)